The analysis of macroeconomic development of the United Kingdom from 2000 to 2018 - Zeman, Mikuláš; Czesaný, Slavoj, 1940-; Klement, Josef, 1990-; Vysoká škola ekonomická v Praze. Národohospodářská fakulta (2019)
The master’s thesis analyzes strengths, weaknesses, opportunities and threats of the UK’s economy from 2000 to 2018. The method of research is the comparison with the average of OECD and Eurozone members. Results of the analysis are stated in SWOT matrix. The master’s thesis also evaluates economic consequences of the Brexit referendum. The analysis shows that the referendum had no important impact on the UK’s macroeconomic fundamentals. The thesis predicts future impacts of Brexit as well. The UK will remain a strong international economy despite its withdrawal from the EU.
Vedoucí práce: Slavoj Czesaný
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Národohospodářská fakulta, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: hospodářská politika [obor dipl. práce]; diplomové práce; master's theses